2008
DOI: 10.1016/j.otohns.2007.10.032
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anesthetic agents on perioperative bleeding during tonsillectomy: Propofol‐based versus desflurane‐based anesthesia

Abstract: Propofol-based anesthesia is a reliable method for use in children who undergo tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(92 reference statements)
0
2
0
1
Order By: Relevance
“…[2] Recently, along with the advancement in anesthetic and surgical techniques, tonsillectomy has become safer than old times. [3] The 2 main drugs among many that are widely used for anesthetic purpose are known to be sevoflurane and remifentanil. [4,5] …”
Section: Introductionmentioning
confidence: 99%
“…[2] Recently, along with the advancement in anesthetic and surgical techniques, tonsillectomy has become safer than old times. [3] The 2 main drugs among many that are widely used for anesthetic purpose are known to be sevoflurane and remifentanil. [4,5] …”
Section: Introductionmentioning
confidence: 99%
“…Esto se explicaría dado que el propofol tendría un efecto dual: procoagulante mediante la estimulación del efecto de las prostaglandinas y anticoagulante por inhibición de la ciclooxigenasa [27]. En 2008, Okuyucu et al, evaluó el sangrado intraoperatorio según el tipo de mantención de la anestesia general (TIVA propofol vs inhalatoria) determinando un menor sangrado con el uso de propofol [28]. A pesar de los resultados contradictorios, estas diferencias en la técnica anestésica suelen carecer de significado clínico.…”
Section: Discussionunclassified
“…The role of anesthetics in bleeding was also examined during tonsillectomy. Okuyucu et al randomized patients undergoing tonsillectomy to either propofol-based anesthesia ( n = 27) or to desflurane-based anesthesia ( n = 33) and demonstrated that propofol-based anesthesia was associated with less measured blood loss [ 11 ]. These studies indicate that an inhalation-based anesthetic technique is associated with more intraoperative bleeding than a propofol-based anesthetic technique for head and neck procedures.…”
Section: Clinical Studiesmentioning
confidence: 99%